1955
DOI: 10.1002/aic.690010428
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment removal by a wire‐mesh separator

Abstract: The efficiency of a wire-mesh separator as an entrainment eliminator has been experimentally determined in an evaporator employing a sodium chloride brine to trace the entrainment throughout the system. Superficial linear velocities have been tested with efficiencies ranging from less than 80% at lower velocities up to 99.9% at 17 ft./sec. Higher superficial linear velocities were explored, but the results were erratic, with reentrainment from the separator visually evident. The experimental data have been cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0
1

Year Published

1959
1959
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 18 publications
3
20
0
1
Order By: Relevance
“…This has been done by electrostatic precipitation of the aerosol followed by gravimetric determination of the deposited mass (Conder and Liew, 1989;Raynor and Leith, 2000), or more recently by capturing the aerosol on a highefficiency filter placed further downstream (Contal et al, 2004;Mead-Hunter et al, 2013;Mullins et al, 2014). Others have used more indirect techniques such as condensation and weighing in the case of water mist (Carpenter and Othmer 1955;El-Dessouky et al, 2000), or even chemical precipitation and titration in the case of sulfuric acid (Bürkholz, 1970). In all these cases, the mass fraction actually obtained depends strongly on the placement of the capturing device downstream of the filter and there is no guarantee of collecting the entire size spectrum.…”
Section: Introductionmentioning
confidence: 98%
“…This has been done by electrostatic precipitation of the aerosol followed by gravimetric determination of the deposited mass (Conder and Liew, 1989;Raynor and Leith, 2000), or more recently by capturing the aerosol on a highefficiency filter placed further downstream (Contal et al, 2004;Mead-Hunter et al, 2013;Mullins et al, 2014). Others have used more indirect techniques such as condensation and weighing in the case of water mist (Carpenter and Othmer 1955;El-Dessouky et al, 2000), or even chemical precipitation and titration in the case of sulfuric acid (Bürkholz, 1970). In all these cases, the mass fraction actually obtained depends strongly on the placement of the capturing device downstream of the filter and there is no guarantee of collecting the entire size spectrum.…”
Section: Introductionmentioning
confidence: 98%
“…Some methods for predicting the separation efficiencies of mesh pads were derived based on the droplet collection efficiency of a single wire, which was related to the Stokes number, Stk. However, in most cases, certain assumptions must be made Paglianti, 2000, 2001;Feord et al, 1993;Langmuir andBlodgett, 1944-1945;Carpenter and Othmer, 1955;Bradie and Dickson, 1969). With the advancements in measurement technologies, researchers have been able to experimentally investigate the relationship between separation efficiency and some macrostructural parameters (pad thicknesses, densities, specific surface areas, porosities, etc.).…”
Section: Introductionmentioning
confidence: 97%
“…Models developed by Brunazzi and Paglianti (2000) following Langmuir and Blodgett efficiency equations (1946) and subsequent modifications (Carpenter and Othmer, 1955), to investigate demister efficiency revealed that calculation of Stokes number using diameter values underestimates collection efficiency of polypropylene strands and overestimates collection efficiency of metal strands.…”
Section: Introductionmentioning
confidence: 99%